Response of some growth traits and yield of barley genotypes Hordeum vulgare L. to planting dates - Al-Muhja, Zahraa Ahmed; Al-Refaiy , Shaimaa Ibrahim (Journal of Kerbala for Agricultural Sciences, 2022)
The experiment was held at the Warka Extension Farm in Al-Muthanna Governorate / Al-Warka District, during the season (2021-2022) to know the response of growth traits and yield of genotypes G1, G2, G3, G4, G5, G6, G7, G8, G9 of barley crop, in addition to Cultivar Aba 265 (G10) for planting dates (1, 10, 20, 30) November, the experiment was applied using randomized complete block design (RCBD)according to the Split- plot method and with three replications, the results of the experiment showed: The two genotypes G4 and G9 were superior in the number of days from planting to 75% of flowering, with the highest averages of (113.75) days, while the two genotypes G6 and G3 were superior in the number of days from 75% flowering to physiological maturity, with their averages reaching (36.58 and 35.08). One day, the genotypes G1, G6, G10, G7 and G8 were recorded without significant difference between them the highest average plant height reached (80.08, 79.98, 79.92, 79.80 and 76.78) cm, respectively. In contrast, genotype G5 recorded the highest average of the leaf area of ​​the flag reached (14.28) cm². For grain yield, the genotype G7 recorded the highest grain yield with an average of (8.427) ton ha-1, and the cultivar Aba 265 (G10) recorded the highest biological yield with an average of (16.75) ton ha-1. The first date (1/11) outperformed in many of the studied traits, as it achieved the highest averages in both plant height and number of days from 75% flowering to physiological maturity, the flag leaf area and vital yield amounted to (84.26) cm, (35.67) days and (14.96) ) cm2 and (16.42) ton ha-1 respectively, and the third date (20/11) was superior in grain yield with an average of (8.014) ton ha-1.